The impact of a multi-specialty team for high risk pulmonary embolism on resident and fellow education. (August 2018) - Elbadawi, Ayman; Wright, Colin; Patel, Dhwani; Chen, Yu Lin; Mazzillo, Justin; Cameron, Pamela; Barnes, Geoffrey D; Cameron, Scott J
The impact of the Pulmonary Embolism Response Team (PERT) model on trainee physician education and autonomy over the management of high risk pulmonary embolism (PE) is unknown. A resident and fellow questionnaire was administered 1 year after PERT implementation. A total of 122 physicians were surveyed, and 73 responded. Even after 12 months of interacting with the PERT consultative service, and having formal instruction in high risk PE management, 51% and 49% of respondents underestimated the true 3-month mortality for sub-massive and massive PE, respectively, and 44% were unaware of a common physical exam finding in patients with PE. Comparing before and after PERT implementation, physicians perceived enhanced confidence in identifying ( p <0.001), and managing ( p =0.003) sub-massive/massive PE, enhanced confidence in treating patients appropriately with systemic thrombolysis ( p =0.04), and increased knowledge of indications for systemic thrombolysis and surgical embolectomy ( p =0.043 and p <0.001, respectively). Respondents self-reported an increased fund of knowledge of high risk PE pathophysiology (77%), and the perception that a multi-disciplinary team improves the care of patients with high risk PE (89%). Seventy-one percent of respondents favored broad implementation of a PERT similar to an acute myocardial infarction team. Overall, trainee physicians at a large institution perceived an enhanced educational experience while managing PE following PERT implementation, believing the team concept is better for patient care.